Non-dissociated <c+a> dislocations in an AZ31 alloy revealed by transmission electron microscopy. Issue 4 (2nd April 2020) - Ma, Luoning; Xie, Kelvin; Cai, John; Hemker, Kevin J.
ABSTRACT: dislocations in pure Mg have been reported to dissociate on basal planes, resulting in a sessile configuration that limits the ductility and formability of Mg. In this study, careful tilting experiments and weak-beam dark-field electron microscopy observations elucidated that dislocations in the commercial alloy AZ31 remain compact without apparent dissociation. The stabilization of the dislocation core structure with Al and Zn alloying may explain the improved strain to failure in the AZ31 alloy as compared to pure Mg samples. GRAPHICAL ABSTRACT: IMPACT STATEMENT: This paper involved detailed TEM analysis to elucidate an overlooked mechanism of non-dissociated dislocations in AZ31 alloy that may contribute to improved ductility.